2016
DOI: 10.1177/0957650916668768
|View full text |Cite
|
Sign up to set email alerts
|

Numerical comparisons of rotordynamic characteristics for three types of labyrinth gas seals with inlet preswirl

Abstract: Numerical results of frequency-dependent rotordynamic force coefficients and leakage flow rates are presented and compared with three types of labyrinth gas seals, which include a tooth-on-stator (TOS) labyrinth seal, a tooth-on-rotor (TOR) labyrinth seal, and an interlocking-tooth (INT) labyrinth seal. These three labyrinth seals represent the typical labyrinth seal designs used in rotating machinery as shaft seals to limit leakage and ensure a robust rotordynamic design. The three labyrinth seals have the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Thorat and Chids showed that the whirl frequency depends significantly on the DC of the labyrinth seals when the Mach number approaches unity [38], or when there is an inlet pre-swirl or when the pressure is very high [38,39]. Additionally, pre-swirl and the rotor whirl speeds have a small effect on the leakage for one-sided and stepped labyrinths [29].…”
Section: Cfd Model Setupmentioning
confidence: 99%
“…Thorat and Chids showed that the whirl frequency depends significantly on the DC of the labyrinth seals when the Mach number approaches unity [38], or when there is an inlet pre-swirl or when the pressure is very high [38,39]. Additionally, pre-swirl and the rotor whirl speeds have a small effect on the leakage for one-sided and stepped labyrinths [29].…”
Section: Cfd Model Setupmentioning
confidence: 99%
“…Based on the porous medium model and whirling rotor method, Zhang et al [22] revealed the effects of operating conditions on rotor dynamic coefficients for the different seal configurations by the numerical model. Wu et al [23] employed the multi-frequency dynamic mesh technique by Li [24] to calculate the dynamic characteristics of various types of seals. Their research examined changes in the dynamic characteristics of different seals, ranging from sub-frequency to super-frequency whirl.…”
Section: Introductionmentioning
confidence: 99%
“…For high pressure and high rotational speed turbomachinery where stability is of concern, because of the limited effective damping offered by labyrinth seal, 6 pocket damper seals were invented and first tested by Vance and Schultz. 7 Different from the labyrinth seal, the pocket damper seals insert or machine partition walls equally spaced around the circumference.…”
Section: Introductionmentioning
confidence: 99%